2021
DOI: 10.32479/ijefi.10634
|View full text |Cite
|
Sign up to set email alerts
|

Study the Efficiency Hypothesis in the Egyptian Stock Market

Abstract: This article aims is to verify if the Egyptian stock market has information efficiency (market efficiency assumptions) by studying the presence of time series properties for daily stock returns between 2005 and 2015. Parametric and non-parametric tests are used to achieve this purpose, such as ADF/ PP unit root-RUNS TEST-Perron -run test. The Jarque-Bera test was used to measure the moderation of returns; the GARCH model and ARCH model are used also. The results referring to the Egyptian stock market follow th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
0
0
Order By: Relevance
“…Overall, the results indicate the inefficiency of the Egyptian market at the semistrong level, as the declaration of COVID-19 has an insignificant negative effect on stock returns, whether on the day of the declaration, before or after it, and this is consistent with previous research (Abdelzaher, 2021; El Ansary and El-Azab, 2017), and the underlying reasons for these results can be referred to the idea that investors are noise trading when making their investment decisions.…”
Section: Discussionsupporting
confidence: 90%
“…Overall, the results indicate the inefficiency of the Egyptian market at the semistrong level, as the declaration of COVID-19 has an insignificant negative effect on stock returns, whether on the day of the declaration, before or after it, and this is consistent with previous research (Abdelzaher, 2021; El Ansary and El-Azab, 2017), and the underlying reasons for these results can be referred to the idea that investors are noise trading when making their investment decisions.…”
Section: Discussionsupporting
confidence: 90%
“…‫عشش‬ ‫انخامس‬ ‫انمدهذ‬ ‫انثاوٍ‬ ‫انعذد‬ -‫إبشَم‬ 0202 020 (Abdelzaher, 2021) aims is to verify market efficiency assumptions within the Egyptian stock market. Daily stock returns between a time series of ten years from 2005 to 2015 was examined in order to test to what extent the Egyptian stock market is efficient.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Elmoghany (2021) conducted an event study and found that the Egyptian stock market reacted positively following the 2016. Additionally, Abdelzaher (2021) provided evidence suggesting that the Egyptian stock market may not be informationally efficient.…”
Section: Literature Reviewmentioning
confidence: 99%